REVITALISASI RUANG TERBUKA HIJAU BOLANGO RIVERSIDE di KECAMATAN HULONTHALANGI, KOTA GORONTALO - Eka, Rahmawati; Salim, Hildawati H. (RADIAL : Jurnal Peradaban Sains, Rekayasa dan Teknologi, 2024)
This study aims to revitalize the Bolango Riverside Green Open Space (RTH) area. The methods used include qualitative and descriptive research, conducted through field surveys to obtain factual information about the condition of the Bolango Riverside Green Open Space in Tenda Subdistrict, Hulonthalangi District, Gorontalo City. The survey was carried out in Tenda Subdistrict from early October to December 2024, beginning with the collection of initial data, followed by observational interviews, and data confirmation with field conditions and local community perspectives. The results of the study indicate that inadequate public facilities, such as parks, hardscape, softscape, public toilets, and increasingly disorganized landscaping, make this green open space less attractive to visitors, both local residents and those from outside Gorontalo. The conclusion of this study is that the Bolango Riverside RTH area has experienced negative impacts, such as waste issues and insufficient infrastructure, necessitating the development of the RTH area. This RTH area has the potential to become a tourist attraction with supportive infrastructure, as its main potential lies in marine resources that can boost the regional economy, benefit the local community, and attract tourists.